Role of School Principals in Integrating Technology into the Teaching–Learning Process - K S P Sisindra; Fareed Mohamed Nawastheen (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The present study explored the role of Sri Lankan school principals in integrating technology into the teaching–learning process across diverse educational contexts. It examined how principals provide leadership, support, and direction for technology use in schools, while also identifying the challenges they face and the factors that influence their efforts. Methodology: A qualitative research design was adopted, using semi-structured interviews with ten school principals from Sinhala, Tamil, and English medium schools across four districts in Sri Lanka. Data were analyzed using thematic analysis Main Findings: The findings reveal that principals play multiple roles as facilitators, enablers, and advocates of technology integration. They support initiatives such as STEM education and encourage teachers’ use of digital tools; however, their leadership is often constrained by the absence of a clear technological vision, limited resources, inadequate infrastructure, teacher resistance, and insufficient awareness of technology-related policies. These challenges vary between urban and rural schools and across different language-medium contexts Novelty/Originality of this study: This study contributes to the understanding of school principals’ roles in leading technology integration in Sri Lankan schools. It highlights both leadership practices and contextual constraints and offers practical insights to strengthen principals’ capacity to support effective and equitable technology-enhanced teaching and learning.